IMPLEMENTATION OF RESTORATIVE JUSTICE IN THE PUNISHMENT OF CORRUPTION CRIMES IN INDONESIA - Zufarnesia; Yasmira Mandasari Saragih (PT. Radja Intercontinental Publishing, 2024)
Indonesia is a rule of law country where one of the basic objectives of eradicating criminal acts of corruption in Indonesia is to restore state losses. However, the retributive justice paradigm which is the legal basis for eradicating criminal acts of corruption and punishing perpetrators of corruption is not relevant to the main goal of the law of eradicating corruption in Indonesia. What is actually important in the spirit of eradicating corruption is that returning state losses is only an additional penalty which can also be replaced by imprisonment. This article is intended to examine the concept of criminal punishment for perpetrators of criminal acts of corruption that is relevant to be implemented in Indonesia in accordance with what is required by law by taking into account developments in the life of the nation and state today. The study focuses on deepening collaboration on the concept of restorative justice to maximize returns to state finances in punishing perpetrators of corruption in Indonesia. By using normative juridical research methods, this study concludes that the concept of restorative justice in punishing perpetrators of criminal acts of corruption can be implemented in the form of strengthening norms for returning state losses from being an additional crime to being a basic crime. To anticipate that the perpetrator will not be able to pay the losses, the concept of forced labor can be applied instead of imprisoning the perpetrator of a criminal act of corruption.